EVALUATION OF IL-6 PRODUCTION BY HUMAN BLOOD CELLS INCUBATED WITH METAL COMPLEXES OF Γ-GLOBULIN - S. B. Cheknev (Medicinskaâ Immunologiâ, 2014)
Abstract. This study has shown that that a common cytokine pool induced in cultured human peripheral blood cells (PBC) supplied by either γ-globulin fraction proteins, copper or zinc cations, or appropriate metal complexes, contains detectable amounts of IL-6 (0.39+0.14 to 2.04+0.16 ng/ml). γ-globulin complexes with zinc or copper ions are able to induce production of IL-6 in amounts differing from those induced by control proteins, or copper and zinc ions used alone. IL-6 production by PBC in presence of γ-globulin/zinc complexes was 1.5 to 2.5-fold higher than with control proteins or single zinc ions at 24, 48 and 72 hrs of observation, whereas IL-6 production by PBC in presence of γ-globulin complexes with copper was higher than with appropriate control proteins or copper ions used alone for 48 and 72 hrs of cell incubation (resp., 1.7 to 2.4 and 2.8 to 4.6-fold increase). Possible role of copper and zinc ions chelated by γ-globulins from the microenvironment and modifying the Fc regions of antibodies, is considered a potential regulatory factor of IL-6 production by human PBC.